Evaluation of BATICH Score for the management of Paediatric Blunt Abdominal Trauma (Journal of Paediatric Surgeons of Bangladesh, 2025)
Introduction: Blunt abdominal trauma is a frequent reason for hospital admission and a significant cause of death in children. Early diagnosis is important to reduce the mortality and morbidity. Computed tomography (CT) scan is currently the best diagnostic, but due to the cost and availability of CT scan, a non-invasive scoring system calculated using readily available parameters such as physical examination findings, abdominal ultrasound, and routine laboratory parameters may be useful. The aim of the study was to evaluate the association of Blunt Abdominal Trauma in Children (BATiCH) score between conservative and operatively treated patients of paediatric blunt abdominal trauma. Methods: It was a hospital based prospective comparative observational study carried out in Paediatric Surgery Department of Chittagong Medical College Hospital (CMCH) from June 2021 to September 2023. Patients with blunt abdominal trauma were enrolled prospectively as per set inclusion and exclusion criteria. Physical examination findings, abdominal ultrasound, and routine laboratory profile were recorded. Patients were discharged when discharge criteria were achieved, and they were followed up for 1 month after discharge. BATiCH score was compared between patients who needed laparotomy and those who were treated conservatively. Results: Mean ±SD BATiCH score was 8.74 ±3.324 in conservative treatment group and 15.25 ±2.315 in surgical treatment group (p7 (P=0.001) Conclusion: BATiCH score was significantly greater in patient who needed laparotomy after blunt abdominal trauma than those of patient, treated conservatively.Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):40-44